2006
DOI: 10.1002/pros.20438
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of arginine methyltransferase CARM1 in androgen receptor function and prostate cancer cell viability

Abstract: CARM1 is essential for AR function and may play a role in prostate cancer progression. CARM1 may represent a novel therapeutic target in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
3
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(103 citation statements)
references
References 37 publications
3
96
3
1
Order By: Relevance
“…These studies suggest that increased expression of PRMT5 is part of the mechanism by which cells become transformed. Similarly, PRMT4 has also been shown to be overexpressed in primary prostate cancer, and reducing its expression in the LNCaP prostate cancer cell line inhibited cell growth and proliferation (Majumder et al, 2006). These findings indicate that alteration of normal histone methylation patterns is associated with cancer in humans and that histone methyltransferases should be considered as good candidates to target in cancer therapy.…”
Section: Regulation Of Prmt Activity and Its Role In Cancermentioning
confidence: 87%
“…These studies suggest that increased expression of PRMT5 is part of the mechanism by which cells become transformed. Similarly, PRMT4 has also been shown to be overexpressed in primary prostate cancer, and reducing its expression in the LNCaP prostate cancer cell line inhibited cell growth and proliferation (Majumder et al, 2006). These findings indicate that alteration of normal histone methylation patterns is associated with cancer in humans and that histone methyltransferases should be considered as good candidates to target in cancer therapy.…”
Section: Regulation Of Prmt Activity and Its Role In Cancermentioning
confidence: 87%
“…For example, the fact that PRMT1 and CARM1 can act as coactivators of nuclear receptors makes them likely candidates to be overexpressed in hormone-dependent cancers, including breast cancer (2). Indeed, it has been found that CARM1 overexpression correlates with androgen independence in human prostate carcinomas (73,74). It has also been observed that increased methylation of a PRMT6 substrate correlated with breast tumors of higher metastatic potential (75,76).…”
Section: Complex Genomic Structure At the 5ј-end Of The Prmt1 Gene Lementioning
confidence: 99%
“…18 The Coactivator Associated Arginine Methyl Transferase (CARM1) was shown to mediate histone H3 methylation at androgen-regulated enhancer elements in response to androgenic stimuli. 19 Histone methylation of AR target sequences can play significant roles in the dynamics of AR binding to cognate sequences. Interestingly, it was shown that bicalutamide, an AR antagonist, can facilitate histone methylation.…”
Section: Ar and Chromatinmentioning
confidence: 99%